SIMULASI KESTABILAN PROTOTYPE UAV-SPRAYER BERBASIS QUADCOPTER TERHADAP PENAMBAHAN SEKAT PADA PENAMPUNG CAIRAN - Hariyanto, Kris; Dirgantara, Bangga (Vortex, 2022)
The use of UAVs has begun to penetrate the world of agriculture. One of the functions of UAVs in agriculture is to spray pesticides. The pesticides used are liquid so that when the UAV is airborne and maneuvering, the fluid experiences fluid motion or sloshing. Sloshing that occurs can cause the balance of the UAV to be disturbed. To overcome this, a bulkhead or baffle is needed in the reservoir in order to reduce fluid movement. In the case of the research studied, the simulation of sloshing in the reservoir with the presence of baffles and without the presence of baffles. This research uses different reservoir variations and different water levels, namely 55 mm, 35 mm and 15 mm. Simulations are carried out during cruising and maneuvering flights at a speed of 2 m/s. The container modeling uses the Catia V5R20 software and the simulation uses the Ansys 14.5 software. The simulation results show that the effect of baffle placement is more visible if the baffle is placed in the xy plane, while for the baffle placement in the yz plane, the force caused by sloshing is greater. In spraying the UAV-Sprayer will more often fly forward (cruise), while for maneuvers (right or left) it is only done occasionally/not too often. So that giving baffles is more effective in the xy plane because it can reduce sloshing better than the baffles in the yz plane.